Enhancing the control of Campylobacter jejuni in a theragnostic approach: FTIR-ATR combined with artificial intelligence, binding-peptides, and the use of chicken embryos as an in vivo model - Braga, Paula Fernanda de Sousa (2024)
Due to the importance to Campylobacter spp. to human health and the high prevalence of C. jejuni (CJ) in chickens, this study aimed to seek alternatives to improve the control of CJ through a theragnostic approach, using the chicken embryo as an important pre-clinical model. The work comprises four chapters regarding Campylobacter jejuni in poultry. The first chapter provides a literature review of Campylobacter spp., highlighting its significance and occurrence worldwide, the pathogenicity of Campylobacter in humans and chickens, prevention, and therapy-based Campylobacter control, as well as its diagnostic. Also, this chapter describes pathogens’ identification by machine learning techniques and phage display technology. The second chapter aimed to evaluate the virulence and infection of strains of CJ isolated from chicken and standard strain isolated from humans to better understand the pathogen-host relationship of CJ and chicken embryo (CE). We also evaluated embryo mortality, weight, gross and microscopic lesions, multiplication of the bacteria in the embryo, macrophage and lymphocyte counting by flow cytometry analysis, cytokine analysis by ELISA, and analysis of histopathological lesions. At low doses, CJ generated lesions in CE, and some strains stimulated the immune system, but the response was strain-dependent, reinforcing the importance of studying the virulence, infection, and immune response of several strains of C jejuni and the CE model as of great utility. Chapter three discusses a quick, practical, and reliable new technique to identify CJ - the ATR-FTIR spectroscopy associated with artificial intelligence to detect Campylobacter jejuni. This technique was a useful tool to identify CJ in real time, with a specificity of 100% using the Random Forest model. The fourth chapter describes a promising alternative for Campylobacter jejuni control through theragnostic approach, using Phage Display-Derived peptides. Besides selecting peptides using the phage display technique, we also performed phages sequencing and the molecular docking to reach the best peptides, which were tested in vitro, in an inhibitory assay and in vivo, using CE as experimental models. We proved that the peptide is efficient for diagnosis approaches, which is interesting because they can be more specific (since they recognize a specific epitope) and safer, once it is not necessary to handle the pathogen and they may be a potential to inhibit CJ. This thesis brings new potential alternatives to study and control CJ in a theragnostic approach.